Lettere a Ruggero Jacobbi Regesto di un fondo inedito con un'appendice di lettere - Bartolini, Francesca (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2006)
Lettere a Ruggero Jacobbi offers an extensive register of over a thousand pieces of letters sent to the author over a period of forty years (from 1938 to 1981) and of about seventy letters written by him to various correspondents, giving an account of all the epistolary material preserved in the Jacobbi Collection of the "Bonsanti Contemporary Archive" of the Scientific Literary Cabinet G.P. Vieusseux of Florence. From the unpublished documents, carefully filed by Francesca Bartolini, the figure of an intellectual among the most significant of the Italian twentieth century emerges, always present in the cultural debates of the time and passionate and responsive towards the literary and theatrical world. Thanks to the many voices which intertwine different countries and ages, we can reconstruct life starting from the years of Hermeticism, to which he was close in his early youth, find traces of the sixteen years spent in Brazil, retrace the last Italian decades, in which he simultaneously exercised the activities of reviewer, director and theatrical author, essayist, literary critic, historian of literature, university professor, poet and director of the Academy of Dramatic Art "Silvio D'Amico". The names that recur are numerous and authoritative, even of senders of Lusitanian and Hispanic culture, testifying to the authoritative presence of Jacobbi on the European scene. Some of these important names are Murilo Mendes, Jorge Amado, Ricardo Cassiano and, among the Italians, Italo Calvino, Alessandro Parronchi, Vasco Pratolini, Salvatore Quasimodo, Vittorio Sereni and Elio Vittorini. In the appendix that closes the volume, the transcription of some letters dealing with writing, criticism, friendship and commitment is proposed.